2002
DOI: 10.1088/0022-3727/35/3/308
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of streamers in pure N2and N2/O2mixtures and a ≈13 cm gap

Abstract: Empirical data on streamer formation and propagation in near-atmospheric pressure N 2 and N 2 /O 2 mixtures are presented. The data were obtained primarily from high-speed, high-sensitivity shutter and streak photography of streamers produced in a ≈13 cm gap. The streamer propagation velocity as a function of applied voltage, polarity, total pressure, and O 2 concentration are provided. In addition, information on streamer bifurcation, and streamer shape and size is included. The breakdown process has two phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
102
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 29 publications
15
102
2
Order By: Relevance
“…The propagation velocity of the ionization front is in the range of 3 × 10 7 to 4 × 10 7 cm/s. We find that the calculated values for the frontal velocities agree well with the experimental results [21][22][23] and with those reported in [20,[24][25][26][27]. Measurements [21,22] of the average propagation velocity of the ionization front extend from 2 × 10 7 to 5 × 10 7 cm/s, the propagation average velocity [24,25] of the ionization wave is approximately of 5 × 10 7 cm/s, which agrees with our results.…”
Section: Resultssupporting
confidence: 91%
“…The propagation velocity of the ionization front is in the range of 3 × 10 7 to 4 × 10 7 cm/s. We find that the calculated values for the frontal velocities agree well with the experimental results [21][22][23] and with those reported in [20,[24][25][26][27]. Measurements [21,22] of the average propagation velocity of the ionization front extend from 2 × 10 7 to 5 × 10 7 cm/s, the propagation average velocity [24,25] of the ionization wave is approximately of 5 × 10 7 cm/s, which agrees with our results.…”
Section: Resultssupporting
confidence: 91%
“…During the 8-8.1 ns time, the streamer travels 0.1 mm, and the average velocity is nearly 10 6 m/s. This result is consistent with the reported experimental results by Yi and Williams [67]. They observed the streamer propagation of the needle-to-plane geometry produced in a short gap (0.5-1 cm) using high-speed photography.…”
Section: Electric Field Distribution and Streamer Propagation Velocitysupporting
confidence: 93%
“…The experimental results showed the steamer reached the cathode in 7 ns, and the average velocity was around 7.14 × 10 5 m/s. According to the experimental results in [67], the values of the speed deduced from various empirical formulas differed by almost one order of magnitude, even under the same experimental condition. In addition, experimental conditions (including gas, gap lengths, and electric field strengths) significantly affect the streamer propagation.…”
Section: Electric Field Distribution and Streamer Propagation Velocitymentioning
confidence: 95%
“…Streamers appear in early stages of atmospheric discharges such as sparks or sprite discharges [1,2]; they also play a prominent role in numerous technical processes. It is commonly observed that streamers branch spontaneously [3,4]. But how this branching is precisely determined by the underlying discharge physics is essentially not known.…”
mentioning
confidence: 99%